‘Strawberry Star’ – A Spotted, Fancy-Leaved Caladium for Use in Containers and Landscapes - Zhanao Deng (EDIS, 2012)
'Strawberry Star' is a fancy-leaved variety with a primarily white leaf face and attractive red spots. It is similar to 'Marie Moir' in leaf color and coloration pattern but different from 'Marie Moir' in petiole color. Compared to 'Marie Moir', 'Strawberry Star' sprouts earlier, produces high-quality container plants, demonstrates better landscape performance, and yields more tubers. These improvements make 'Strawberry Star' a desirable replacement for 'Marie Moir' and an additional sun-tolerant variety for the landscape plant palette. This 5-page fact sheet was written by Zhanao Deng and published by the UF Department of Environmental Horticulture, August 2012.